Female reproductive impacts of dietary methylmercury in yellow perch (Perca flavescens) and zebrafish (Danio rerio). (March 2018) - DeBofsky, Abigail R.; Klingler, Rebekah H.; Mora-Zamorano, Francisco X.; Walz, Marcus; Shepherd, Brian; Larson, Jeremy K.; Anderson, David; Yang, Luobin; Goetz, Frederick; Basu, Niladri; Head, Jessica; Tonellato, Peter; et al.
Abstract: The purpose of this study was to evaluate the effects of environmentally relevant dietary MeHg exposures on adult female yellow perch ( Perca flavescens ) and female zebrafish ( Danio rerio ) ovarian development and reproduction. Yellow perch were used in the study for their socioeconomic and ecological importance within the Great Lakes basin, and the use of zebrafish allowed for a detailed analysis of the molecular effects of MeHg following a whole life-cycle exposure. Chronic whole life dietary exposure of F1 zebrafish to MeHg mimics realistic wildlife exposure scenarios, and the twenty-week adult yellow perch exposure (where whole life-cycle exposures are difficult) captures early seasonal ovarian development. For both species, target dietary accumulation values were achieved prior to analyses. In zebrafish, several genes involved in reproductive processes were shown to be dysregulated by RNA-sequencing and quantitative real-time polymerase chain reaction (QPCR), but no significant phenotypic changes were observed regarding ovarian staging, fecundity, or embryo mortality. Yellow perch were exposed to dietary MeHg for 12, 16, or 20 weeks. In this species, a set of eight genes were assessed by QPCR in the pituitary, liver, and ovary, and no exposure-related changes were observed. The lack of genomic resources in yellow perch hinders the characterization of subtle molecular impacts. The ovarian somatic index, circulating estradiol and testosterone, and ovarian staging were not significantly altered by MeHg exposure in yellow perch. These results suggest that environmentally relevant MeHg exposures do not drastically reduce the reproductively important endpoints in these fish, but to capture realistic exposure scenarios, whole life-cycle yellow perch exposures are needed. Highlights: Effects of MeHg on yellow perch (YP) and zebrafish (ZF) reproduction were studied. Whole life-cycle MeHg exposure effects on YP reproduction was modeled using ZF. With RNA-seq, many genes were affected in ZF, but using QPCR, most genes in ZF and YP not significantly affected. Chronic dietary MeHg exposures had minimal impact on ovarian development and reproduction in both species. Impacts of whole life-cycle MeHg exposure on YP necessitates future research.